Notes that transgress: an archive to know - Medeiros, Vanise (2021)
The 19th century is an important period for understanding the historicity of the language on Brazilian soil. Anchored in the theoretical field of the History of Linguistic Ideas (Auroux) in relation to that of Discourse Analysis (Pêcheux, Orlandi), in this article, we aim to inform about the composition of an archive built from the footnotes of Alencar in two of his novels, O Guarani and Iracema, totaling 202 entries. These notes, on words and expressions, refer to the language and act as entries. Our position is that Alencar's notes are part of the intense production of vocabularies of the 19th century in Brazil, not only as word lists, but in the exhaustive work of the one who captures, describes and interprets them. This archive will allow different studies on the language in the 19th century, as well as work on reflections on the writer's place in the grammatization of the language on Brazilian soil.